2020
DOI: 10.1186/s13018-020-01994-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in skin RNA of horses affected with degenerative suspensory ligament desmitis

Abstract: Background Equine degenerative suspensory ligament desmitis (DSLD) is a systemic connective tissue disorder first identified in Peruvian Paso horses but afflicting other horse breeds as well. Inappropriate accumulation of proteoglycans in connective tissues, most prominently in tendons and ligaments, leads to progressive and debilitating lameness and pain. It is largely unknown what drives the overproduction of proteoglycans, but our previous studies suggest involvement of bone morphogenetic pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…Collagen VI is an extracellular matrix protein with critical roles in maintaining muscle and skin integrity ( Lamande and Bateman 2018 ). The role of COL6A5 mutations in the development of myopathy and fibrosis is not understood ( Sabatelli et al 2011 ), but the expression of COL6A5 is decreased in the skin of DSLD-affected horses ( Haythorn et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen VI is an extracellular matrix protein with critical roles in maintaining muscle and skin integrity ( Lamande and Bateman 2018 ). The role of COL6A5 mutations in the development of myopathy and fibrosis is not understood ( Sabatelli et al 2011 ), but the expression of COL6A5 is decreased in the skin of DSLD-affected horses ( Haythorn et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During past decades, investigation of the molecular pathology of DSLD, disturbances to signaling pathways, genome-wide analysis with low-density markers, and case–control gene expression analysis have been performed ( Young et al 2018 ; Mero and Pool 2002 ; Haythorn et al 2020 ). A low-resolution genome-wide association study (GWAS) in the PH identified candidate loci on Equus caballus autosomes (ECAs) 6, 7, 11, 14, and 26 that did not meet genome-wide significance ( Strong 2005 ; Metzger and Distl 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ADAM12 is also implicated in processes of excessive growth, such as cardiac hypertrophy [ 38 ]. IGSF10, a pro-inflammatory cytokine, is down-regulated in calcific aortic valve disease [ 39 , 40 ]. SGCD is associated with aortic pathology [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin dysregulation associated with EMS and PPID 27,35,112,113,[149][150][151][152][153] Suspensory ligament desmitis/degeneration PPID 119,120,154,155 Muscle atrophy and possible secondary back pain PPID 24,26,75,126 Obesity and lameness, exercise intolerance Obesity, EMS due to suppression from high circulating levels of glucocorticoids, the clinical significance of which is unknown. 39 In humans, hypothyroidism is more clinically significant but only has a weak link to MetS in men.…”
Section: Endocrinopathic Laminitismentioning
confidence: 99%